2019
DOI: 10.1177/1545968319893298
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Spinal Cord Stimulation and Motor Rehabilitation in Spinal Cord Injury: A Systematic Review

Abstract: Background. Epidural spinal electrical stimulation at the lumbar spinal level evokes rhythmic muscle activation of lower-limb antagonists, attributed to the central pattern generator. However, the efficacy of noninvasive spinal stimulation for the activation of lower-limb muscles is not yet clear. This review aimed to analyze the feasibility and efficacy of noninvasive transcutaneous spinal cord stimulation (tSCS) on motor function in individuals with spinal cord injury. Methods. A search for tSCS studies was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 45 publications
1
78
0
Order By: Relevance
“…To date, the vast majority of studies have fixed the intensity of tSCS by using the subjective perception of sensations made by participants or more directly by detecting muscle contraction in response to the stimulus [ 6 ]. Recently, Serrano-Munoz et al [ 54 ] demonstrated the practical limitations of adjusting the intensity of stimulation current based on subjective perception and highlighted the importance of defining objective parameters to adjust current intensity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, the vast majority of studies have fixed the intensity of tSCS by using the subjective perception of sensations made by participants or more directly by detecting muscle contraction in response to the stimulus [ 6 ]. Recently, Serrano-Munoz et al [ 54 ] demonstrated the practical limitations of adjusting the intensity of stimulation current based on subjective perception and highlighted the importance of defining objective parameters to adjust current intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also revealed that tSCS mediates several therapeutic effects in subjects with neurological impairments [ 6 ]. Thus, tonic tSCS, applied as a biphasic rectangular current at a frequency of 30–50 Hz, has shown a therapeutic potential to enhance voluntary motor activity [ 7 , 8 ], trunk stability [ 9 ], standing [ 10 ], gait function [ 7 , 11 , 12 ] and as a method to reduce spasticity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations